Light steel recycled concrete structure formwork-free integrated construction and long-acting protection technology

CN122942598APending Publication Date: 2026-10-20北京聚嫄智能环保科技发展有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611190705.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

相对于现阶段轻钢骨料混凝土BIM装配式墙体施工体系,本发明提供了解决如下关键技术难题

Benefits of technology

本专利为整套轻钢双腔体再生轻骨料混凝土墙体基础方案,下述特征均为区分现有技术的核心创新点:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of green prefabricated building technology, and discloses a formwork-free integrated construction and long-term protection process for light steel recycled concrete structures, solving the problems of low precision, complicated procedures, and easy hollowing of plaster in traditional light steel walls. It uses BIM thermal calculation to match the outer cavity thickness, CNC machining of double-row light steel keels (error ≤1mm, QR code etching), and assembly to form a double-cavity structure; the inner cavity is poured with ≥850kg / m³ recycled aggregate concrete, and the outer cavity is poured with ≥200kg / m³ recycled insulating concrete, followed by initial setting and finishing, 72h undisturbed curing, 12h±1h high-pressure slurry sealing, and 24h±2h structured plastering. The outer cavity is adapted to 65%~near-zero energy consumption and is compatible with high corrosion and high seismic resistance scenarios. This invention combines three curing processes, saving ≥40% water; plaster bonding strength ≥1.2MPa, hollowing rate 0%; recycled aggregate content ≥70%, six-fold anti-corrosion guarantee 30~100 years of lifespan, and digital delivery adapts to the needs of intelligent construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical fields of green prefabricated buildings, ultra-low energy consumption building construction, water-saving green construction and building industrialization. Specifically, it relates to a standardized, formwork-free prefabricated construction process that can achieve safe, corrosion-resistant, durable, energy-saving and heat-insulating lightweight steel aggregate concrete composite wall structures with 50 years of long-term performance without degradation, while simultaneously achieving significant water savings, substantial reduction in labor input, structural upgrade of plaster layer quality, and structural and integrated permanent molding of the plastering process. Background Technology

[0002] The current BIM-based prefabricated wall construction system for light steel aggregate concrete consists of: factory-prefabricated light steel keel + aggregate concrete integrated wall panels, transported to the site for assembly and splicing, followed by post-casting / bolted connection of joints, pipeline pre-embedding, surface layering, and acceptance. It is generally divided into five stages: preliminary planning, factory prefabrication, component storage and transportation, on-site assembly and construction, surface layer finishing, and final acceptance. The following breakdown of the process and core tasks for each stage is provided. For ease of comparison when describing this invention later, the existing technology is described in full here: Currently, there are related patents for light steel keel + lightweight concrete cast-in-place (CN201310510142.8 Light steel structure lightweight concrete cast-in-place wall and construction method, CN201410104997.5 Construction method of green energy-saving cast-in-place thermal insulation composite exterior wall system), which use fiber cement / calcium silicate templates fixed on both sides of the keel and pour foamed concrete inside to form a sandwich wall. Although there is similarity to the materials of this invention, the underlying technical route has a fundamental shortcoming: 1) Single-layer homogeneous filling, without load-bearing or thermal insulation functional zones. Concrete is only used for filling and cannot bear load independently. It must be attached to the external beam and column frame. 2) The side panels need to be installed in layers, which is a complicated process and the efficiency of integrated construction is low; 3) Without the installation of a timed mortar sealing and structured plaster double-layer anti-corrosion and airtight barrier, the risk of light steel corrosion and wall permeability and water seepage is high; 4) Without BIM energy-saving parameter linkage variable thickness design logic, the thermal insulation performance cannot be matched to the full standard of 65% to near zero energy consumption as needed.

[0003] Horizontal quantitative comparison table of existing technologies.

[0004] Summary of common defects in existing systems: 1) The insulation is installed externally at the rear, and its service life is seriously out of sync with the 50-year main body. Multiple replacements and repairs are costly and pose a high risk of high-altitude operations. 2) Plastering is a post-decorative process. The carbonization of the base layer results in extremely low bonding strength, and hollowing and cracking are common occurrences. The lifespan of the surface layer is less than one-third of that of the main body. 3) The construction process is complex, requiring the cooperation of various professional technicians, resulting in high labor costs and low standardization; 4) The concrete, plaster and surface layer are cured by watering multiple times, which results in a large loss of water resources and does not meet the evaluation standards for green construction. 5) Later pipeline renovations involving trenching and chiseling cause irreversible structural damage to the walls and insulation; 6) The consumption of steel bars, formwork, and insulation boards is large, and the carbon emissions in the physicalization stage are relatively high, which does not meet the requirements of the construction industry's dual-carbon transformation.

[0005] Currently, the vast majority of patents revolve around this modern building system, such as CN202121960780.6 Prefabricated building single-panel low-energy-consumption enclosure structure, etc. However, the improvements of these existing technologies are all in the physical structure. The improvements are made in the entire construction process, the enclosure and lateral force resisting components, or the physical connection method of the keel frame, such as CN202010376905.4 Integral sprayed wall structure with inner and outer molds. There has been no revolutionary technological innovation.

[0006] The authorized invention CN114154217A - A BIM model attribute verification method and system based on BIM model data standards - discloses a BIM model verification method for engineering projects, but it is only used to compare each component of the BIM model to be verified with the components in the BIM model data standard component library to check whether the components match. Summary of the Invention

[0007] Technical problems to be solved Compared to the current BIM-based prefabricated wall construction system using lightweight steel aggregate concrete, this invention provides solutions to the following key technical challenges. (1) The traditional three separate watering maintenance, large evaporation loss and serious water waste are solved by combining the three maintenance into one and saving more than 40% of water in total; (2) Traditional plastering is a decorative process, which is detached from the structure, has common problems such as hollowing and cracking, and unstable quality. This invention upgrades the above-mentioned plastering process into an integrated molding process of the main structure, so that the plaster layer has structural protection properties. (3) The problem of redundant manual input in traditional processes, such as fragmented operations, repetitive work, multiple maintenance and repairs, is greatly reduced by reducing labor hours and construction costs. (4) Early disturbance of recycled lightweight aggregate concrete causes microcracks and original structural damage; (5) Problems such as wall shrinkage cracking, airtightness failure, and gradual decline in energy-saving performance; (6) The industry's shortcomings include water seepage and air permeability in the pores of the non-removable mesh formwork, corrosion of light steel, and insufficient durability; (7) Irreversible structural damage caused by later slotting and modification, so as to achieve structural integrity and no damage throughout the entire life cycle of the building.

[0008] This invention innovatively constructs a brand-new industrialized construction system that combines 72-hour rigid, undisturbed centralized curing with immediate grout finishing and simultaneous closed-loop forming of three layers: structure, grout, and plaster.

[0009] Three core disruptive innovations: Water-saving innovation: The traditional three-stage water curing process for concrete, mortar, and plastering is combined into a single centralized and balanced curing process, eliminating repeated watering and saving more than 40% of water in the same period. Cost reduction and efficiency improvement through innovation: Eliminating scattered manual processes such as formwork removal, secondary cleaning, multiple maintenance, and post-repair, significantly reducing labor input, compressing cross-operations, and lowering construction costs; Structural attribute innovation: It completely changes the industry's inherent model of "plastering as a decorative process", upgrades the plastering process of recycled lightweight aggregate concrete walls and incorporates it into the main structural construction system, so as to achieve synchronous hydration, synchronous forming, synchronous stress and service life of plaster layer and structural layer, and fulfill the structural construction commitment of structured, integrated and permanent plastering process.

[0010] This invention establishes a new construction paradigm for prefabricated walls that are structurally integrated, water-saving, require less labor, have high quality, and have a long lifespan.

[0011] Technical effect This patent presents a complete lightweight steel double-cavity recycled lightweight aggregate concrete wall foundation solution. The following features are the core innovative points that distinguish it from existing technologies: (1) Dual-cavity layered synchronous molding structure The inner cavity is uniformly fixed at 150mm, while the outer cavity is matched with a corresponding thickness according to the energy-saving level. The inner and outer cavities are poured and hydrated and cured simultaneously in layers, and there are no construction cold joints at the cavity interface. This is the core structural feature that distinguishes this solution from commercially available double-cavity walls.

[0012] (2) High-precision machining control standards for components The overall component processing error is ≤1mm; the implementation path is: CNC cold bending forming, online synchronous punching, and precise cutting to a fixed length.

[0013] (3) Component life cycle weather resistance traceability QR code identification Three mandatory conditions must be met: the QR code must be etched on a non-load-bearing area of ​​the component; the code must be bound to a unique component ID and a complete set of on-site installation parameters; and the weather resistance of the markings must meet the requirements for stable identification over a 50-year service life of the building.

[0014] (4) Fully mechanical connection, weld-free assembly system The entire set of light steel components does not use welding technology and is assembled entirely with bolts, rivets, and clips; the materials of the connectors are limited to high-galvanized steel or SUS304 stainless steel.

[0015] (5) Setting parameters of high galvanized reinforced expanded metal mesh The galvanized layer thickness is ≥120g / ㎡; the height of the V-shaped reinforcing ribs is 10 / 15mm and the rib spacing is 90 / 110mm; the long side of the mesh is 10 / 20mm and the short side is 5 / 10mm; the vertical spacing of the mesh clips is ≤300mm and the horizontal spacing is ≤400mm; all dimensional parameters are key restrictions to avoid counterfeiting.

[0016] (6) Dual-cavity synchronous layered casting process and material specifications The thickness of a single layer of concrete pouring is ≤1500mm; the pouring standard is that the surface is covered with slurry and there are no air bubbles inside; the fixed density and thermal conductivity of the recycled lightweight aggregate concrete in the inner and outer cavities are specified simultaneously.

[0017] (8) 72-hour rigid undisturbed integrated curing process Three layers of strict constraints: During the 72-hour curing cycle, it is forbidden for people to walk on the site, pile up materials, or place construction equipment to cause disturbance; the amount of water replenished per unit area at one time is controlled at 2~3L.

[0018] (7) High-pressure slurry sealing process for 12±1 hours Three key parameters are required: spraying pressure 0.5 / 0.8MPa; total thickness of sealing layer 3 / 5mm; cement-to-ultrafine sand ratio 1:0.5 / 3.0 and water-cement ratio 0.40 / 0.45. All three parameters are indispensable.

[0019] (9) Structured layered plastering process with a sealing layer of 24±2 hours Layering indicators: total plaster thickness 10 / 15mm, base layer 6 / 8mm, top layer 4 / 7mm; redispersible latex powder content in mortar 3 / 6 parts; standard bond strength of plaster layer after 28 days ≥1.2MPa. Attached Figure Description

[0020] Figure 1 This is a standardized construction flow chart of the process of this invention; Figure 2 This is a three-dimensional schematic diagram of the double-cavity wall keel in an embodiment of the present invention; Figure 3 This is a three-dimensional schematic diagram of the double-cavity wall frame in an embodiment of the present invention; Figure 4 This is a schematic diagram of pipeline nodes in an embodiment of the present invention; Figure 5 This is a three-dimensional schematic diagram of the double-cavity wall keel in an embodiment of the present invention; Figure 6 This is a schematic cross-sectional view of the double-cavity wall keel in an embodiment of the present invention; Figure 7This is a schematic diagram of the structure of the galvanized wire mesh mold that does not require disassembly in an embodiment of the present invention. Detailed Implementation

[0021] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. The following embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.

[0022] It should be noted that all embodiments are based on the core five-step process of the present invention (skeleton design and assembly → initial setting slurry finishing → 72h rigid undisturbed curing → 12h±1h high-pressure slurry sealing → 24h±2h structured plastering), and the parameters not specifically mentioned are consistent with those in Embodiment 1.

[0023] Example 1 - Construction of residential walls to achieve 75% energy efficiency (conventional application scenario) Application scenario: A 200mm thick outer wall of a certain affordable housing project exceeds the 75% energy saving requirement (heat transfer coefficient ≤0.35W / (m²·K)) in the "General Specification for Energy Conservation and Renewable Energy Utilization in Buildings" GB 55015-2021.

[0024] Step 1: Digital Design and Skeleton Assembly The double-cavity structure (inner cavity 150mm, outer cavity ≥110mm) is formed by fixing the galvanized mesh mold on both sides of the double-row light steel keel. The double cavity is mainly composed of the inner row of light steel keel and the outer row of light steel keel. The dual-cavity lightweight steel-aggregate concrete wall breaks down climate and geographical barriers, constructing a globally applicable high-performance building envelope system. The inner cavity is load-bearing and earthquake-resistant, while the outer cavity intelligently adjusts its thickness based on BIM thermal calculations, adapting to extreme cold and heat, and readily meeting energy consumption standards from 75% to near-zero (U-value ≤ 0.345). Integrating structure, insulation, and protection, it completely eliminates organic insulation materials, possessing freeze-thaw resistance, Class A fire resistance, and 50-year long-term corrosion resistance, ending exterior wall peeling and dampness, providing the ultimate barrier for prefabricated buildings worldwide with the same lifespan and zero maintenance.

[0025] Each inner row of light steel keel has a unique spatial coordinate with the outer row of light steel keel. Electromechanical pipelines are pre-embedded according to BIM coordinates, with no welding and zero grooving throughout the entire process. This step is the structural premise of this invention.

[0026] Specifically, the following steps are included: 1.1) Determine the parameters of the double-cavity wall according to the building energy efficiency grade, the fixed thickness of the inner cavity is 150mm, and the outer cavity is matched with the corresponding minimum thickness according to the energy efficiency standard: 65% energy efficiency ≥110mm, 75% energy efficiency ≥150mm, ultra-low energy consumption ≥400mm, and near-zero energy consumption ≥650mm; the software automatically generates the processing data of the inner and outer double rows of light steel keels, which are processed on the numerical control production line using S350 aluminum-zinc coated structural steel, with a comprehensive processing error ≤1mm; 1.2) BIM data export and keel processing: Start the Revit software, and import the pre-planned building construction model. Conduct collision detection on the full-professional models of architecture, structure, and electromechanics. According to the 75% energy efficiency standard in GB 55015-2021 (heat transfer coefficient ≤0.35W / (m²·K)), the software can automatically calculate and lock the thickness of the outer cavity (in a certain example, it is 150mm). Thereby, the keel layout data (including coordinates, spacing, and opening positions) is exported to the CNC numerical control production line. The production line uses S350 aluminum-zinc coated structural steel (double-sided aluminum-zinc coating weight 150g / m², yield strength 355MPa) for cold bending forming, with real-time laser calibration during the processing to ensure that the comprehensive processing error of the keel is ≤1mm.

[0027] 1.3) On-site assembly of double-row keels: Clean the base layer of the floor slab, and snap the wall positioning axis and the keel control line.

[0028] The worker scans the QR code ID with a handheld terminal to obtain the installation instructions, and assembles the inner row light steel keels 3 and the outer row light steel keels 4 according to the spatial coordinates bound to the QR code ID of each keel obtained in step 1.2).

[0029] The butt joints of the light steel keels are fastened with SUS304 stainless steel bolts, the bolt spacing is ≤400mm, the fastening torque is controlled at 45~50N·m, and welding is strictly prohibited throughout the process to avoid damaging the zinc coating. The keel webs are separated to form independent double-cavity spaces. The double-row keels are fixed by web connecting ribs to form a stable "eye"-shaped frame, so as to form the double cavities.

[0030] 1.4) Laying of non-demountable galvanized mesh formwork and double-cavity isolation: Lay the non-demountable galvanized mesh formwork on both sides of the keel. In a specific engineering project, the galvanized layer of the mesh formwork is ≥120g / m², the mesh 52 has a long side of 15mm and a short side of 8mm, the height of the V-shaped rib 51 is 12mm, the rib spacing is 90-110mm, and the V-shaped ribs face the concrete pouring side. The non-demountable galvanized mesh formwork is fixed to the keel without welding using special stainless steel spiral nails, with a vertical fixing spacing of 90-110mm and a horizontal fixing spacing of ≤400mm.

[0031] Preferably, the overlap width of the mesh is 10-120mm, and the overlap is fixed with stainless steel spiral nails. When the mesh overlaps horizontally, the V-shaped ribs of the mesh overlap the upper and lower layers, and the fixing spacing is ≤400mm. When the mesh overlaps vertically, it should overlap on the vertical keel, and the fixing spacing is 90-110mm. The upper and lower layers are laid with staggered joints, and continuous joints are strictly prohibited.

[0032] Dual-cavity isolation structure: such as Figure 1 As shown, the inner metal mesh mold is fixed by the vertical keel on the inner side of the exterior wall, and the outer metal mesh mold is fixed by the vertical keel on the outer side of the exterior wall. The web of the keel acts as a physical separation barrier between the inner and outer cavities, and the mesh mold itself forms a closed mold cavity. The inner and outer cavities are physically completely independent through the double isolation of "keel web + non-removable galvanized mesh mold", preventing the two types of concrete with huge differences in density from mixing during subsequent pouring.

[0033] 1.5 Pre-embedded electromechanical pipelines: Based on the BIM model positioning, the pre-embedded pipeline 10 (JDG pipe, wall thickness ≥1.5mm) is fixed to the keel web or the inside of the mesh formwork using clips, with a clip spacing ≤500mm. Custom-made extended boxes are used at the junction box location, ensuring the box opening is flush with the outer surface of the mesh formwork. The box is sealed around its perimeter with sealant to prevent grout leakage. Only after the concealed work has passed inspection can the next process proceed.

[0034] The effect of "Step 1: Assembly of formwork and skeleton" is as follows: ① Stability of the dual-cavity structure: Through the dual isolation structure of "keel web plate + non-removable mesh formwork", the 150mm load-bearing structure in the inner cavity and the 150mm insulation structure in the outer cavity are completely independent. There is no concrete cross-contamination or cold joints during the simultaneous pouring of the dual pumps. The overall shear bearing capacity of the wall reaches 68kN / m, which is 18% higher than that of the traditional single-cavity light steel wall. ② Construction accuracy assurance: CNC machining + BIM pre-embedded positioning, keel processing error ≤1mm, electromechanical pipeline pre-embedded deviation ≤4mm, wall flatness after completion ≤3mm / 2m, no need for secondary leveling, and can directly carry out finishing construction, saving about 40% of the labor cost of leveling process; ③ Anti-corrosion base construction: No welding throughout the process + stainless steel fasteners, the galvanized layer of light steel keel is free from high temperature burns, avoiding damage to the anti-corrosion layer from the source, and laying the physical foundation for the subsequent six-fold anti-corrosion system; ④ Solid waste disposal infrastructure: The recycled aggregate content reaches 72%, and approximately 420 kg of building demolition waste can be disposed of per cubic meter of wall, which meets the requirements of the "Technical Specification for Resource Utilization of Construction Waste" GB / T 25177-2010.

[0035] 2.1 Dual-cavity synchronous layered casting: A dual-pumping system is employed, with two independent feed pipelines. Aggregate concrete 6 (density 850 kg / m³, slump 180 ± 20 mm) is pumped into inner cavity 1; recycled insulating concrete 7 (density 200 kg / m³, thermal conductivity 0.055 W / (m²·K), recycled aggregate content 75%, slump 200 ± 20 mm) is pumped into outer cavity 2. Key procedures: The thickness of each layer is strictly controlled to ≤1500 mm. During pouring, a designated person taps the outside of the formwork to check for voids or incomplete filling areas.

[0036] 2.2 Determination of initial setting window and removal of laitance: After pouring, start the timer. During the initial setting window of 1.5 to 3 hours (on-site judgment standard: when you press your finger on the concrete surface, the indentation depth is 1 to 2 mm and it is not sticky), carry out finishing work.

[0037] 2.3 Low-pressure water mist humidification: Within 5 minutes of cleaning the laitance, use a low-pressure sprayer (atomization pressure 0.1~0.2MPa) to evenly moisten the wall surface. The standard for moistening is that the wall surface is uniformly moist and glossy, without any standing water, to prevent plastic shrinkage cracks from forming in the surface concrete due to excessive water loss.

[0038] Step Two: Technical Effects of "Pre-Setting Slurry Finishing" ① Improved surface density: During the initial setting window, precise removal of laitance and retention of a 1.8mm protective layer resulted in a wall surface compressive strength of 28.5MPa, an improvement of 15.2% compared to traditional processes (without finishing). ② Control of plastic cracks: Timely humidification with low-pressure water mist, surface concrete water loss rate ≤3%, plastic shrinkage crack incidence rate during construction stage is 0, while the plastic crack incidence rate under the same conditions of traditional process reaches 12.7%; ③ Workability assurance of aggregate concrete: layered pouring + high-frequency vibration, uniform distribution of recycled aggregate, internal cavity concrete dispersion rate ≤5%, external cavity insulation concrete dry density deviation ≤2%, meeting design requirements.

[0039] Step 3: 72-hour construction-undisturbed curing (determines structural strength and micro-crack control) 3.1 Full coverage with moisturizing film: Within 30 minutes of pouring, immediately cover the entire wall with a double layer of 0.12mm thick polyethylene moisture-retaining film. The overlap width of the film should be ≥100mm, and the overlap should be sealed with special tape. The bottom should be tightly pressed against the pre-reserved groove in the ground to form a sealed moisture-retaining space.

[0040] 3.2 Definition and Implementation of Rigid Unperturbed Motion: Initiate a 72-hour curing cycle. Here, "rigid and undisturbed" is defined as the external disturbance acceleration borne by the wall during the curing cycle being ≤0.5m / s². No wall mounting, material stacking, or machine vibration is permitted. Maintain constant temperature and humidity with minimal water replenishment within the membrane, thereby combining the three curing processes of aggregate concrete, the cement slurry sealing layer in step four, and the plaster layer in step five into a single water-locking curing process. Assistance measures: A 1.5m wide rigid warning barrier will be erected on both sides of the wall, with "No Climbing, No Loading" warning signs displayed; flexible buffer pads will be installed between the scaffolding and the wall for physical isolation, prohibiting any personnel from working on the wall; high-vibration machinery operations (such as impact drills and tampers) are strictly prohibited near the wall. Accelerometers will be installed on-site to monitor wall vibration in real time, and an alarm will sound immediately if vibration exceeds the limit.

[0041] 3.3 Temperature and humidity monitoring and hydration: Wireless temperature and humidity sensors are installed inside the moisture-retaining membrane, recording data every 2 hours. The relative humidity inside the membrane is controlled to be ≥85%, and the temperature is controlled between 22~26℃. If the humidity inside the membrane is lower than 85%, a small amount of water is added through the reserved water replenishment holes using a syringe injection method, with the single water replenishment volume per unit area controlled at 2.6L / m². This step combines the three independent processes of traditional aggregate concrete curing, mortar sealing layer curing, and plaster layer curing into a single centralized water-locking curing, resulting in a measured overall water saving of 41.7%.

[0042] Step 3: The effect of "72h construction-free curing" ①Significant water-saving benefits: The traditional three independent processes of "structural curing + mortar curing + plastering curing" are combined into one centralized water-locking curing process, with a water consumption of only 3.4L per unit area, saving 41.7% of water compared to the traditional process. This meets the highest score requirement for "water saving and water resource utilization" in the "Green Building Evaluation Standard" GB / T 50378-2019. ② Microcrack control: Rigid undisturbed curing (external disturbance acceleration ≤0.5m / s²) ensures full hydration of concrete, and the number of microcracks in the wall at 28 days is ≤0.2 cracks / m², which is 92.3% less than the number of microcracks in traditional early disturbance curing (construction can begin after 24 hours); ③Strength Improvement: Under 72 hours of continuous moist curing, the hydration degree of concrete reaches 78%, and the 28-day compressive strength reaches 32.5 MPa, which is 8.2% higher than the strength of the wall after traditional three-stage curing, fully meeting the C30 structural design requirements.

[0043] Step 4: 12h±1h after pouring, high-pressure grout sealing (determines airtightness and corrosion prevention) 4.1 Determination of the window period: 12 hours after pouring (with an error of no more than ±1 hour), the concrete has reached its final set and hydration level of 28%, and the surface capillaries are in a fully connected state, which is the best window for closed operation.

[0044] 4.2 Preparation and spraying of the slurry: Preparation of high-pressure slurry: Cement: Ultrafine sand = 1:0.5 (mass ratio), water-cement ratio 0.43, add 4% redispersible latex powder and 0.7% polycarboxylate superplasticizer, stir evenly and let stand for 5 minutes to defoam. Key actions: Use a 0.65MPa high-pressure airless sprayer, maintain a 90° angle between the nozzle and the wall surface, 30-40cm away from the wall surface, and move at a uniform speed in an "S" shaped trajectory. Spray in 2 coats: The first coat is 2mm thick and dries for 30 minutes; the second coat is applied to a total thickness of 4.2mm. The slurry must completely fill the mesh pores and surface capillaries, with a penetration and anchoring depth of 2.3mm.

[0045] Mechanism verification: If construction is carried out earlier than 11 hours, the concrete has not fully set, and the high-pressure cement slurry will wash away the surface aggregate; if construction is carried out later than 13 hours, the capillaries self-close, and the cement slurry penetration depth is less than 0.5 mm. 12 hours ± 1 hour is the optimal window.

[0046] Step 4: Effect of high-pressure slurry sealing for 12h±1h ① Full pore filling: High-pressure slurry penetrates and anchors to a depth of 2.3mm, the mesh pore filling rate is ≥95%, the capillary pore sealing rate of the wall surface reaches 98%, and the impermeability grade is improved to P8, which is 3 times more impermeable than traditional unsealed walls; ② Corrosion protection barrier construction: The water vapor permeability coefficient of the slurry layer is ≤1.5×10⁻¹¹ g / (m·s·Pa), and the oxygen permeability coefficient is ≤2.1×10⁻¹ 7 cm² / s, effectively blocking external moisture and oxygen from penetrating into the light steel keel, providing a second layer of protection for the six-fold anti-corrosion system; ③ Verification of the necessity of the window period: Through comparative experiments, construction earlier than 11 hours will cause the slurry to wash away the surface aggregate, and the surface aggregate exposure rate will reach 12%; construction later than 13 hours will result in the slurry penetration depth being only 0.4 mm due to the self-sealing of capillaries, and the sealing effect will decrease by 62%. 12 hours ± 1 hour is the only optimal construction window.

[0047] Step 5: 24h±2h after pouring, apply structured polymer plaster (determines the lifespan of the plaster layer). 5.1 Determination of the window period: 24 hours after pouring (with an error of no more than ±2 hours), the hydration degree of the concrete reaches 42%, and the surface CSH gel is still in the active growth period, which is the best time for the plaster layer to form chemical bonds with the main structure.

[0048] 5.2 Preparation and application of polymer plastering mortar: Preparation of polymer-resistant crack-resistant plastering mortar: 100 parts PO 42.5 cement, 235 parts medium and fine sand, 4.8 parts redispersible latex powder, 0.75 parts polycarboxylate superplasticizer, 0.45 parts HPMC, and 1.2 parts polypropylene crack-resistant fiber. Dry mix thoroughly, then add water and stir, controlling the consistency to 70-80 mm. Key steps: Apply a 12 mm thick plaster layer 9, applied in two layers: a 7 mm base layer, using a scraper to press firmly, ensuring the mortar is embedded in the grooves of the V-shaped ribs 51 of the mesh mold, forming a mechanical interlock; a 5 mm top layer, applied before the base layer initially sets, with the surface smoothed and compacted.

[0049] 5.3 Formation of symbiotic structures: The plaster layer, the mortar layer, and the main concrete form a symbiotic structure: A 24h±2h window period is defined after pouring, and the V-shaped ribs of the non-removable galvanized mesh are mechanically interlocked. The measured pull-out bond strength after 28 days is ≥1.2 MPa, with cohesive failure, proving that the plaster layer and the main structure have formed a symbiotic load-bearing structure in an engineering sense. Secondly, the mechanical interlocking involves the plaster mortar embedding into the grooves of the V-shaped ribs of the mesh, forming a physical bond. After 28 days of curing, the measured bond strength between the plaster layer and the base layer reaches 1.31 MPa, far exceeding the average level of 0.4 MPa for traditional plastering, with a hollow rate of 0%.

[0050] Step 5: Effect of Structured Polymer Plastering (24h±2h) ①Structural integration: Through the dual mechanism of "CSH gel cross-layer chemical bonding + mesh V-shaped rib mechanical locking", the plaster layer and the main structure form a symbiotic system. The 28-day bonding strength reaches 1.31MPa, which is 244.7% higher than that of traditional plastering (average 0.38MPa). The plaster layer is upgraded from a "decorative layer" to a "load-bearing layer", which can participate in the wall's impact resistance and wind pressure resistance. ② Significantly improved crack resistance: The polymer plaster layer has a drying shrinkage rate of only 0.021%, which is 74.4% lower than that of traditional cement mortar plaster (0.082%). There are no visible drying shrinkage cracks within 6 months after construction, and the hollow rate is 0%, while the hollow rate of traditional processes under the same conditions reaches 18.7%. ③ Long-term stable performance: After the plaster layer is redispersible latex powder film-forming, it can withstand more than 50 freeze-thaw cycles with a mass loss rate of ≤3%, which is twice that of traditional plastering and meets the long-term use requirements of cold northern regions.

[0051] Step Six: Digital Delivery Throughout the construction process, all mechanical and electrical conduits, junction boxes, and hangers were automatically positioned using BIM software, with a pre-embedded position deviation of ≤4mm and a pipe clamp spacing of 480mm. 100% concealed acceptance was completed before pouring, and the walls were left ungrooved and unchilled throughout their entire lifecycle after completion. Upon completion, a complete set of BIM digital twin models and QR code archives were delivered, supporting component traceability and status monitoring during later operation and maintenance phases.

[0052] The basic effect corresponding to the "six-fold anti-corrosion system" Through six lines of defense—aluminized zinc keel, galvanized mesh, double-cavity concrete wrapping, mortar sealing, structured plastering, and zero grooving—and simulated by a 5% NaCl salt spray accelerated corrosion test, the corrosion rate of light steel components is ≤12% after 30 years, meeting the 50-year design service life requirement for ordinary residential buildings. Under the same conditions, the corrosion rate of traditional light steel walls reaches 35% after 10 years.

[0053] The effect of this basic embodiment is achieved by adapting the basic process to the external cavity parameters (150mm thick insulation layer) of a 75% energy-saving standard, providing targeted benefits for this type of scenario: 1-Energy saving meets the standard: The measured value of the overall heat transfer coefficient of the wall is 0.33W / (m²·K), which is better than the 75% energy saving requirement of ≤0.35W / (m²·K) in the "General Code for Energy Conservation and Renewable Energy Utilization in Buildings" GB 55015-2021. The heating energy consumption is reduced by 31.3% compared with the traditional 24-wall design. 2. Sound insulation performance: The weighted sound insulation of airborne sound reaches 46dB, which meets the requirement of ≥40dB for the partition wall of residential buildings in the "Code for Sound Insulation Design of Civil Buildings" GB 50118-2010, and is 21.1% better than the traditional light steel wall (sound insulation 38dB); 3-Fire resistance: The fire resistance limit of the wall reaches 2.1h, meeting the Class I fire resistance requirements for residential buildings in the "Code for Fire Protection Design of Buildings" GB 50016-2014. Under fire, the temperature rise rate of the light steel keel is reduced by 60% compared with the traditional light steel wall without plaster protection. 4- Construction efficiency: The construction cycle of a single wall (from formwork to plastering) is only 48 hours, which is 20% shorter than the traditional step-by-step process of "formwork + formwork removal + curing + plastering + curing", and the labor cost per square meter is reduced by 35%.

[0054] Basic Effect Verification Comparison Table Explanation of the sustainability of the effect: According to the accelerated aging test, the wall performance of this basic embodiment has a 50-year degradation rate of ≤10%: the thermal insulation performance degradation rate is ≤8%, the structural strength degradation rate is ≤7%, and the plaster layer bonding strength degradation rate is ≤12%, which fully meets the requirements of the entire life cycle of the building and does not have the common problems of traditional walls such as "later plaster peeling, light steel corrosion, and thermal insulation failure".

[0055] This basic embodiment is the baseline implementation of the present invention. All process parameters and operating steps are the minimum implementation standards of the present invention. Subsequent preferred embodiments are all optimized based on this. The technical effect verified in this case is the general basic guarantee effect of the present invention. All effects can be achieved by repeating the aforementioned process actions.

[0056] Preferred Implementation Example 2: Description of Near-Zero Energy Building Scenario Note: This preferred embodiment fully utilizes the process flow, timing control, and general technical effects (such as 41.7% water saving and achieving the required plaster bonding strength) of Basic Embodiment 1. However, it further limits and optimizes specific steps of Basic Embodiment 1 to address the extreme requirements of near-zero energy buildings for thermal performance and airtightness. Any steps not mentioned (such as QR code embedding, no welding requirements, and 72-hour curing time) are the same as in Basic Embodiment 1.

[0057] By further defining steps 1.1, 1.2, 1.3, 2.1, 2.2, 2.3, 3.1, 3.2, 3.3, 4.2, and 5.2 of the basic embodiment 1 below, this preferred embodiment successfully solves the two core technical problems that the basic process cannot overcome in near-zero energy consumption scenarios: uncontrolled thermal bridging in thick insulation layers and difficulty in achieving high airtightness. It achieves excellent performance indicators of a heat transfer coefficient of 0.147 W / (m²·K) and n50 = 0.55 times / h. In this embodiment, step 1.1 is further defined as follows: BIM thermal bridge optimization and external cavity thickness locking; Based on the BIM modeling and keel processing flow of the basic implementation example 1.1, further refinement is carried out in the thermal engineering aspect: Based on the near-zero energy consumption standard (heat transfer coefficient ≤ 0.15 W / (m²·K)), the BIM software automatically locks the outer cavity thickness to 650 mm (150 mm in the basic embodiment).

[0058] For thermal bridge areas such as door and window openings and internal and external corners, the software automatically generates special nodes with an outer cavity thickness of up to 700mm to ensure that the heat transfer coefficient of the thermal bridge area is ≤0.17W / (m²·K).

[0059] In this embodiment, step 1.2 is further defined as follows: the keel is reinforced to resist lateral displacement. Based on the double-row keel assembly process of the basic embodiment 1.2, the keel arrangement parameters are adjusted as follows: Due to the increased thickness of the outer cavity leading to increased lateral pressure on the concrete, the spacing between the double-row light steel keel was reduced from 600mm to 400mm.

[0060] The remaining operations (such as bolt tightening torque of 45~50 N·m, welding is strictly prohibited) are the same as in the basic example 1.2.

[0061] In this embodiment, a further limitation is made to step 1.3: the mesh is tensioned to prevent bulging; Based on the non-removable mesh formwork laying process of the basic embodiment 1.3, a tensioning process is added: Add a bidirectional tensioner to pre-tension the mesh, with the tension force controlled at 50~80N to ensure that the mesh is not loose or bulging; reduce the spacing of the vertical buckles from 280mm to 250mm to resist the lateral pressure of 650mm thick concrete and prevent the mesh from bulging outward.

[0062] After the pipeline pre-embedding in the basic embodiment 1.3 is completed and before the concealed acceptance, a special airtightness procedure 1.3.0 is added: All pipes passing through walls must be fitted with closed-cell rubber and plastic special airtight sleeves. The gap between the sleeve and the wall is sealed by a double sealing process of "filling with flame-retardant polyurethane foam and wrapping with 2 layers of butyl rubber airtight tape". The junction box is filled with airtight sealant, and the gap between the box and the mesh is fully covered with sealant.

[0063] Concealed inspection requirements: There must be ≤2 weak points in airtightness within a 100㎡ area.

[0064] Step 2: Finishing the slurry before initial setting Further definition of step 2.1: Thin-layer casting and application of ultra-lightweight concrete Based on the principle of dual pumping and layered casting in the basic embodiment 2.1, the casting parameters and materials are adjusted as follows: Adjustment of pouring strategy: Due to the increase in the thickness of the outer cavity to 650mm, in order to prevent the accumulation of hydration heat, the thickness of the single layer pouring is reduced from 380mm to 300mm, and a "thin layer pouring, multiple covering" strategy is adopted.

[0065] Material adjustments: The density of the recycled insulating concrete poured in the outer cavity was reduced from 260 kg / m³ to 210 kg / m³, the thermal conductivity was optimized to 0.043 W / (m²·K), and the recycled aggregate content was increased to 78%.

[0066] Vibration parameter adjustment: Due to the decrease in concrete density and the increase in porosity, the vibration time is extended from 15~20s to 25s, and the spacing between vibration points is reduced from ≤300mm to ≤250mm until no large air bubbles overflow.

[0067] Further definition of step 2.2: Low-strength concrete surface protection: Based on the timing of slurry removal (initial setting window period) in the basic embodiment 2.2, the operation intensity and standards are adjusted: since the strength of the ultra-light concrete in the outer cavity is only C5 (the foundation is C10), the cleaning intensity is adjusted to "gentle scraping"; the thickness of the protective layer is adjusted from 1.8mm to 1.5mm, and it is strictly forbidden to damage the low-strength surface structure with excessive force.

[0068] Further limitations on step 2.3: Anti-powdering wetting control Based on the low-pressure spray equipment used in the basic embodiment 2.3, the humidity control target is adjusted: the humidity standard is still based on the wall surface having a uniform gloss and no water accumulation.

[0069] Step 3: 72-hour construction-free curing Further refinement of step 3.1: Thicken the coating — Based on the full coverage process of the moisturizing film in the basic embodiment 3.1, the material specifications are improved: the thickness of the polyethylene moisturizing film is increased from 0.12mm to 0.15mm to improve the heat preservation and moisturizing performance.

[0070] The overlap width has been increased from ≥100mm to ≥150mm to enhance sealing performance.

[0071] Further restrictions on step 3.2: Strict control of temperature difference and vibration — Based on the definition of "rigid and undisturbed" (acceleration ≤ 0.5 m / s²) in the basic embodiment 3.2, temperature control measures are added: the width of the warning fence is increased from 1.5 m to 2 m; Distributed temperature sensors were added on site to monitor the temperature difference between the core and surface of the thick wall in real time, control the internal and external temperature difference to ≤25℃, and start micro-water replenishment for cooling when the limit is exceeded.

[0072] Further restrictions on step 3.3: Encrypted monitoring Based on the temperature and humidity monitoring and water replenishment mechanism of the basic embodiment 3.3, the monitoring frequency is increased: The frequency of temperature and humidity monitoring has been increased from once every 2 hours to once every 1 hour.

[0073] The standard for controlling relative humidity inside the membrane has been raised from ≥85% to ≥90%.

[0074] Step 4: High-pressure grout sealing 12h±1h after pouring Further constraints on step 4.2: Construction of a high-permeability gas barrier layer: Based on the high-pressure spraying process and the "12h±1h" window period of the basic embodiment 4.2, the mixing ratio and construction parameters are adjusted to construct a highly airtight gas barrier layer: Mixing ratio adjustment: The mass ratio of cement to ultrafine sand was adjusted from 1:2.8 to 1:2.6 to improve the coverage of the slurry.

[0075] Spraying parameters were adjusted: the spraying pressure was increased from 0.65MPa to 0.7MPa, and the total thickness was increased from 4.2mm to 4.8mm.

[0076] Target effect: Ensure that the mortar penetration depth reaches 2.6mm, completely fills the large pores of the ultra-lightweight concrete, the mesh pore filling rate is ≥98%, and the water vapor transmission coefficient is ≤1.2×10⁻¹¹g / (m·s·Pa).

[0077] Step 5: 24h±2h after pouring, apply structured polymer plaster. Based on the "chemical bonding + mechanical interlocking" construction principle of the basic example 5.2, the plastering structure is optimized to enhance crack resistance: The total thickness of the plaster layer increased from 12mm to 15mm.

[0078] The structure has been adjusted to a three-layer structure consisting of a 9mm bottom layer, an internal 160g / m² alkali-resistant fiberglass mesh, and a 6mm top layer.

[0079] The overlap width of the mesh fabric should be ≥100mm, and the plastering mortar should fully wrap the mesh fabric to suppress the shrinkage stress of the thick wall plaster layer.

[0080] Example 3: Highly Corrosive Environment Scenarios This preferred embodiment, while fully adopting the process flow, timing control, and general technical effects (such as 41.7% water saving, achieving the required plaster bonding strength, and a six-fold anti-corrosion system for the foundation) of Basic Embodiment 1, further limits and optimizes specific steps of Basic Embodiment 1 to address the pain points of long-term corrosion protection for steel structures in high-salt-spray and high-chloride-ion environments such as coastal mudflats and chemical industrial parks. Steps not mentioned (such as BIM processing error control, 72-hour curing time, and the principle of structured plastering) are the same as in Basic Embodiment 1.

[0081] Step 1: Digital Design and Skeleton Assembly Based on the double-row keel assembly, bolt tightening (torque 45~50 N·m), and strict prohibition of welding throughout the process, using the same steps 1.3 of the basic embodiment, the corrosion resistance of the materials is improved: The material of the light steel keel has been upgraded from S350 aluminum-zinc coated steel (double-sided aluminum-zinc coating amount of 150g / m²) to S350GD+AZ aluminum-zinc coated steel (double-sided aluminum-zinc coating amount of 275g / m²), and the salt spray tolerance time has been increased from the basic 2000h to 5000h.

[0082] All exposed connectors have been upgraded from SUS304 stainless steel to SUS316 stainless steel (molybdenum content ≥2%, with twice the resistance to chloride ion pitting corrosion compared to SUS304).

[0083] After the bolts are tightened, apply epoxy coal tar anticorrosion sealant with a thickness of ≥0.5mm to the bolt head to block the penetration path of water vapor and chloride ions.

[0084] Based on the basic implementation method 1.4, which involves non-removable mesh installation, dual-cavity isolation, and pipeline pre-embedding, an electrochemical corrosion prevention measure is added: The thickness of the galvanized layer of the non-removable galvanized wire mesh has been increased from ≥120g / m² to ≥275g / m². A polytetrafluoroethylene insulating gasket has been added between the wire mesh and the keel buckle to avoid electrochemical reactions caused by contact between different metals.

[0085] After the pipeline is pre-buried, three zinc alloy sacrificial anode blocks (purity ≥99.995%) are pre-buried in the concealed part where the wall meets the ground at the bottom. Through the principle of "sacrificial anode cathodic protection", the zinc blocks are consumed first to protect the light steel keel.

[0086] All contact points between the pre-buried pipelines and the keel are wrapped with insulating tape to completely cut off the electrochemical corrosion path.

[0087] Step 2: Finishing the slurry before initial setting (This step follows the basic implementation methods 1.3 and 1.4 without further limitations. Only the chloride ion content of the recycled insulation concrete in the outer cavity is controlled to be ≤0.01%, which meets the requirements for highly corrosive environments in the "Code for Design of Concrete Structures" GB 50010-2010.) Step 3: 72-hour construction-free curing (This step follows the process described in Basic Example 1.4 without further limitations. Only the chloride ion content of the curing water is controlled to be ≤200mg / L to avoid introducing corrosive media during the curing process.) Step 4: High-pressure grout sealing 12h±1h after pouring Based on the "12h±1h" window period, 0.65MPa spraying pressure, and two-coat spraying process of the basic embodiment 4.2, the slurry ratio is optimized to achieve chemical rust inhibition: The slurry mix ratio is adjusted to: cement: ultrafine sand = 1:2.8, water-cement ratio 0.43, with the addition of 3% migratory rust inhibitor (MCI), 4% redispersible latex powder, and 0.7% polycarboxylate superplasticizer.

[0088] Migratory rust inhibitors can penetrate to the surface of light steel keel with the slurry, forming a monomolecular protective film with a thickness of ≥5nm, which inhibits the corrosion of zinc plating by chloride ions; at the same time, the penetration depth of the slurry is increased from the basic 2.3mm to ≥2.8mm, the mesh pore filling rate is ≥99%, and the chloride ion diffusion coefficient is reduced to ≤1.0×10⁻¹²m² / s.

[0089] Step 5: 24h±2h after pouring, structured polymer plastering. Based on the "chemical bonding + mechanical interlocking" construction principle and a total thickness of 12mm used in the basic example 5.2, the impermeability of the plaster layer is improved: Adding 2% silane hydrophobic powder to polymer plastering mortar makes the contact angle of the plaster layer ≥110°, which has the hydrophobic effect of lotus leaves and further blocks water vapor penetration.

[0090] After the plaster layer is completed, a penetrating crystalline anti-corrosion coating (0.3 kg / m²) is applied to the surface to fill the micropores of the plaster layer, thereby improving the impermeability grade from the basic P8 to P12.

[0091] Step Six: Digital Delivery (This step follows the process of the basic embodiment 1.6 without further limitations. The only difference is the addition of a "corrosion protection layer status monitoring" module to the digital archive, which periodically uses QR codes to trace and monitor chloride ion permeation data and sacrificial anode consumption.) Verification of the effect of preferred embodiment 3 (compared with basic embodiment 1) Further technical problems solved by this preferred embodiment: It solves the problem that the zinc coating of the basic process is completely consumed in 5 to 10 years in a high salt spray environment, which cannot meet the design life of more than 50 years in high corrosion scenarios. This solves the problem of electrochemical corrosion of light steel caused by the inability of physical isolation alone to prevent chloride ion penetration in the basic process; This solves the safety hazard of pitting corrosion and breakage of ordinary stainless steel connectors in the acidic environment of chemical industrial zones during basic processes.

[0092] [Preferred Embodiment 4] High Seismic Fortification Zone Scenario Note: This preferred embodiment, while fully adopting the process flow, timing control, and general technical effects (such as 41.7% water saving, achieving the required plaster bonding strength, and a six-fold anti-corrosion system) of Basic Embodiment 1, further limits and optimizes specific steps of Basic Embodiment 1 to address the core pain point of brittle shear failure and connection node failure in walls of high seismic fortification areas of intensity 8 and above (such as the Sichuan-Tibet earthquake zone, the key fortification area of ​​Beijing-Tianjin-Hebei, and multi-frequency earthquake zones) under major earthquakes. Steps not mentioned (such as the 72-hour curing time and the principle of high-pressure slurry sealing) are the same as in Basic Embodiment 1.

[0093] Step 1: Assembly of formwork and frame Based on the double-row keel assembly, bolt tightening (torque 45~50 N·m), and strict prohibition of welding throughout the process of the basic embodiment 1.3, the shear resistance and ductility of the frame are strengthened: The spacing between the double-row light steel keel was increased from 400mm to 250mm to improve the shear bearing capacity of the wall in the plane.

[0094] The proportion of the recycled aggregate concrete in the inner cavity was adjusted to: 880 kg / m³ density, with 2% straight steel fibers (35 mm in length and 0.55 mm in diameter) added, which gave the concrete high toughness and increased the ultimate tensile strain from 0.01% of the foundation to 0.05%, giving it the characteristic of "cracking but not breaking".

[0095] In addition to bolt fastening, L-shaped reinforcing steel plates (3mm thick, 100mm×100mm in size) are added to the keel joints. The steel plates are fixed to the keel with no less than 4 self-tapping screws to improve the joint's pull-out and shear resistance under cyclic loads.

[0096] Based on the basic implementation method 1.4, which involves non-removable mesh formwork laying, double-cavity isolation, and pipeline pre-embedding, a flexible connection concept is introduced to absorb seismic energy: At the connection points between the top of the wall and the main structural beam, and the bottom of the wall and the ground ring beam, a neoprene rubber damping pad with a thickness of ≥10mm is added. The width of the pad is the same as the wall thickness, allowing the wall to undergo a relative displacement of ±5mm under seismic action, thus avoiding stress concentration that could lead to joint tearing.

[0097] The height of the V-shaped ribs in the mesh mold was increased from 12mm to 15mm, and the rib spacing was reduced from 50mm to 40mm, which enhanced the mechanical interlocking force between the mesh mold and the concrete, allowing the plaster layer to better coordinate with the deformation of the wall.

[0098] All pre-embedded pipelines should be fitted with flexible joints (such as flexible metal hoses) where they pass through walls to prevent pipeline breakage due to wall deformation.

[0099] Step 2: Finishing the slurry before initial setting (This step follows the same process as the basic embodiments 1.3 and 1.4 without further limitations. The only key point is to ensure that the steel fibers are evenly distributed, without clumping or directional arrangement during vibration.) Step 3: 72-hour construction-free curing (This step follows the process described in Basic Example 1.4 without further limitations. It ensures that the steel fiber reinforced concrete is fully hydrated under moisturizing curing to exhibit its high toughness properties.) Step 4: High-pressure grout sealing 12h±1h after pouring (This step follows the process described in Basic Example 4.2 without further limitations. The sealing layer mainly serves to prevent water and corrosion, and has little impact on the seismic performance of the structure.) Step 5: 24h±2h after pouring, apply structured polymer plaster. Based on the "chemical bonding + mechanical interlocking" construction principle of the basic example 5.2, the ductility and energy dissipation capacity of the plaster layer are significantly improved: The total thickness of the plaster layer has been increased from 12mm to 15mm, and a three-layer structure of "9mm bottom layer + built-in 160g / m² alkali-resistant fiberglass mesh + 6mm top layer" has been adopted.

[0100] The amount of redispersible latex powder in polymer plastering mortar was increased from 4.8 parts to 6 parts, further improving the mortar's flexibility (compression-flexural ratio ≤ 3.0).

[0101] When laying the mesh fabric, it is required to be 100% wrinkle-free, and the overlap width is increased from 100mm to 200mm to ensure that the mesh fabric can fully play the role of "tensile reinforcement" and restrain the development of cracks in the plaster layer.

[0102] After construction, the plaster layer has "extensibility". Under an interlayer displacement angle of 1 / 250 (8-degree rare earthquake standard), only hairline micro-cracks appear, without peeling or falling off.

[0103] Step Six: Digital Delivery (This step follows the process of basic embodiment 1.6 without further limitations. It is possible to simply add a "structural health monitoring" module to the digital archive, pre-embed fiber optic grating sensors, and monitor the strain and crack development of the wall under seismic loads in real time.) Verification of the effect of Example 4 (compared with the basic Example 1) Further technical problems solved by this preferred embodiment: It solves the problem of brittle shear failure of light steel keel wall structure under rare earthquakes due to insufficient frame stiffness and rigid connection of nodes; The problem of brittle aggregate concrete in basic processes, which is prone to crushing and damage under earthquakes, has been solved by using steel fiber reinforcement to achieve "crack-free" properties. It solves the problem that the plaster layer of the basic process is prone to cracking and peeling when the interlayer displacement angle is large, and the cost of post-earthquake repair is high. Through flexible connection and high toughness surface layer structure, it gives the wall good energy dissipation capacity and recovery performance.

[0104] Thus far, this specification has described the basic implementation of this technology through a hierarchical structure consisting of one basic embodiment and three preferred embodiments: Basic Implementation Example 1: A universal process chassis (dual-cavity structure + five-step sequence) was established, which solved common quality problems in buildings and is applicable to ordinary residential buildings.

[0105] Preferred embodiment 2: By refining steps 1.1 / 1.2 / 1.3 / 2.1 / 3.1 / 4.2 / 5.2, the problem of near-zero energy consumption and thermal bridging and airtightness of thick insulation layers is solved.

[0106] Preferred embodiment 3: By refining steps 1.2 / 1.3 / 4.2 / 5.2, the problem of chloride ion corrosion and century-old corrosion prevention is solved in highly corrosive environments.

[0107] Preferred embodiment 4: By refining steps 1.2 / 1.3 / 5.2, the problem of brittle failure and insufficient toughness under major earthquakes is solved in high seismic fortification areas.

[0108] The present invention has the following innovative features: Innovation 1: Dual-cavity integrated thermal insulation and load-bearing layered functional design It features a unique dual-cavity functional partition structure, with the inner cavity being high-strength aggregate concrete dedicated to load-bearing and the outer cavity being lightweight insulating concrete dedicated to energy saving. Through adjustable keel spacing, it meets all standards for energy saving from 65% to near-zero energy consumption. The dual cavities are poured simultaneously, with no cold joints or thermal bridges at the interface, and the structure and insulation are completely integrated.

[0109] Innovation 2: Ultra-high precision CNC machining at the millimeter level (≤1mm) The fully CNC production line is integrated and molded, with a comprehensive processing error of ≤1mm, which is far superior to the industry's conventional accuracy of ±2~5mm. The components are standardized, interchangeable, and require no on-site repairs, resulting in extremely high engineering consistency.

[0110] Innovation 3: Full-process weld-free assembly connection system The keel, mesh, and embedded parts are all mechanically connected by bolts, rivets, and clips, with zero welding throughout the process. The aluminum-zinc / galvanized protective layer of the light steel is fully preserved, eliminating material deterioration and corrosion defects from the source.

[0111] Innovation 4: Precise process of 12h+24h hydration overlap timing By utilizing the golden window period from the initial setting to the stable hydration of concrete, a two-layer process of 12-hour mortar sealing and 24-hour structured plastering is superimposed, and the three-layer structure is simultaneously hydrated and chemically bonded, completely solving the problem of delamination and hollowing between layers.

[0112] Innovation 5: 72-hour rigid, undisturbed, centralized curing It pioneered a three-step, three-curing-in-one model, replacing the traditional three separate water spraying curing methods. It provides full-area, sealed water-locking curing, saving over 40% of water while ensuring full hydration of concrete and eliminating original micro-cracks.

[0113] Innovation Six: Upgrade of Plastering Structure Function It revolutionizes the industry by transforming plastering from a post-decorative layer into a structurally supporting layer that cures, bears load, and has the same lifespan as the main structure, significantly improving the overall integrity and crack resistance of the wall.

[0114] Innovation 7: Six-layer composite long-lasting anti-corrosion protection system The integrated aluminum-zinc coated light steel substrate, high-galvanized mesh protection, double-cavity concrete wrapping, 12-hour slurry pore sealing, 24-hour structured plaster sealing, and fully pre-embedded zero-grooving non-destructive structure provide six layers of protection, ensuring that the light steel components will not rust for 50 years and the walls will have an ultra-long service life.

[0115] Innovation 8: Fully BIM-based Digital Automated Design + Digital Twin Management Later, it can be seamlessly integrated with dedicated 3D design software to automatically complete keel splitting, node generation, opening reinforcement, parameter matching, pipeline positioning, and output all data digitally; the unique QR code of each component is bound to the 3D coordinates, installation parameters, and quality inspection information to build a full-process digital twin construction system.

[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions created by the present invention, and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions created by the present invention without departing from the essence and scope of the technical solutions created by the present invention.

Claims

1. A formwork-free integrated construction and long-term protection process for lightweight steel recycled concrete structures, characterized in that, Includes the following steps: Step 1: Digital Design and Skeleton Assembly – Based on BIM thermal calculations, match the outer cavity thickness and export the data to the CNC production line to process double-row light steel keel; fix the non-removable galvanized mesh molds on both sides of the keel to form inner and outer cavities respectively, and pre-embed electromechanical pipelines according to BIM coordinates, with no welding and zero grooving throughout the process; Step 2: Pre-setting grouting and finishing - The dual pumping system independently pours aggregate concrete into the inner and outer cavities respectively. During the initial setting window of 1.5 to 3 hours after pouring, the laitance of the mesh mold is cleaned, a 1 to 2 mm protective layer is retained, and the wall surface is moistened with low-pressure water mist. Step 3: No less than 72 hours of undisturbed curing – After pouring, a 72-hour undisturbed curing no-go zone is set up, prohibiting wall installation, material stacking, and machinery vibration. The membrane is kept at constant temperature and humidity with a small amount of water added, thereby combining the three curing processes of aggregate concrete, the slurry sealing layer in step 4, and the plaster layer in step 5 into a single water-locking curing process. Step 4: 12h±1h after pouring, high-pressure slurry sealing - high-pressure spraying of slurry fills the mesh pores and capillaries on the concrete surface. Step 5: After pouring for 24h±2h, apply structured plaster in layers. The bottom layer of mortar is squeezed and embedded into the V-shaped ribs of the mesh to form a mechanical interlock. The top layer is smoothed and compacted before the bottom layer initially sets. The total thickness of the plaster is 10~15mm. Thus, the plaster layer, concrete, and mortar layer form a co-existing stress structure. The 28-day interfacial bond strength is ≥1.2MPa. Curing continues for 72h, and the curing period ends.

2. The process according to claim 1, characterized in that: The galvanized mesh formwork has a galvanized layer of ≥120g / m² and is provided with V-shaped ribs facing the concrete pouring side. The V-shaped ribs are 10~15mm high and 90~110mm apart. The galvanized mesh formwork is fixed to the keel without welding by clips.

3. The process according to claim 1, characterized in that: In step two, the inner cavity is filled with recycled aggregate concrete with a density ≥ 850 kg / m³, and the outer cavity is filled with recycled thermal insulation concrete with a density ≥ 200 kg / m³. In step four, the slurry is made of cement: ultrafine sand = 1:0.5~1:3.0, water-cement ratio 0.40~0.45, with 4% redispersible latex powder and 0.7% polycarboxylate superplasticizer added. It is sprayed in 2~3 coats using a 0.5~0.8MPa high-pressure airless sprayer, with a total thickness of 3~5 mm.

4. The process according to claim 1, characterized in that: In step five, the total thickness of the plaster layer is 10-15mm, divided into a base layer of 6-9mm and a top layer of 4-7mm. When plastering the base layer, the mortar is squeezed into the groove of the V-shaped rib to form a mechanical lock. The top layer plastering is completed before the base layer initially sets and is smoothed and compacted.

5. The process according to claim 1, characterized in that: The thickness of the outer cavity is linked to the building's energy efficiency rating: 65% energy saving ≥ 110mm, 75% energy saving ≥ 150mm, ultra-low energy consumption ≥ 400mm, and near-zero energy consumption ≥ 650mm.

6. The process according to claim 5, characterized in that, When applied to near-zero energy building scenarios: In step one, the spacing between the double-row light steel keel is increased to ≤400mm, and a two-way tensioning process is added to the mesh laying, with a tension force of 50~80N; In step two, the outer cavity is poured with ultra-lightweight thermal insulation concrete with a density of 200kg / m³ and a thermal conductivity of 0.043W / (m²·K), and the thickness of a single layer is reduced to 300mm; In step four, the ratio of cement paste to ultra-fine sand is adjusted to 1:2.6, the spraying pressure is increased to 0.7MPa, and the total thickness is increased to 4.8mm; In step five, the plaster layer structure is a 9mm base layer + an inner 160g / m² alkali-resistant fiberglass mesh + a 6mm surface layer.

7. The process according to claim 1, characterized in that, When applied to highly corrosive environments: the double-row light steel keel has a double-sided aluminum-zinc coating of ≥275g / m², the connectors are made of SUS316 stainless steel, zinc alloy sacrificial anode blocks are pre-embedded at the bottom of the wall, and polytetrafluoroethylene insulating washers are installed between the mesh and the keel clips; in step four, a migration-type rust inhibitor accounting for 3% of the cement mass is added to the slurry; in step five, 2% silane hydrophobic powder is added to the plaster mortar, and a penetrating crystalline anti-corrosion coating is applied to the surface of the plaster layer.

8. The process according to claim 1, characterized in that, When applied to high seismic fortification zones: in step one, the spacing between the double-row light steel keel is increased to ≤400mm, a rubber damping pad layer of ≥10mm thickness is provided at the connection between the wall and the main structure, and an L-shaped reinforcing steel plate is added at the keel joint and fixed with no less than 4 self-tapping screws.

9. The process according to claim 6, characterized in that: In step one, all pipes passing through the wall are fitted with closed-cell rubber and plastic airtight sleeves, and the gap between the sleeve and the wall is sealed by a double sealing process of filling with flame-retardant foaming agent and wrapping with airtight tape; in step three, the thickness of the moisturizing film is increased to 0.15mm, the relative humidity control standard inside the film is improved to ≥90%, and the frequency of temperature and humidity monitoring is increased to once every 1 hour.

10. The process according to claim 1, characterized in that, It also includes a six-layer composite long-term anti-corrosion protection system, which consists of: (1) the aluminum-zinc coated substrate of the double-row light steel keel; (2) the zinc coated layer of the non-removable galvanized mesh; (3) the aggregate concrete wrapping layer of the inner and outer cavities; (4) the high-pressure slurry sealing layer formed in step four of claim 1; (5) the polymer plastering layer formed in step five of claim 1; and (6) the electromechanical pipeline is pre-embedded with full BIM, with no welding and zero trenching during construction.

Citation Information

Patent Citations

  • Lightweight steel construction lightweight concrete cast-in-place wall and construction method

    CN103556758A

  • Construction methods for green and energy-saving cast-in-place thermal insulation composite exterior wall systems

    CN103883026B

  • Integral sprayed wall structure with inner and outer molds

    CN111535484B

  • Fabricated building one-plate low-energy-consumption enclosure structure

    CN215563551U